Some of the Creations of Olim Otaxon Specific Characteristics - Anvar Allambergenov (Zien Journals, 2022)
This article talks about a series of short stories of the writer Olim Otakhan. Some of his works are analyzed and the creative features of the author are discussed. The author's translations are also acknowledged throughout the article.
Keywords: Olim Otakhan's work; style; symbol; genre